Numeracy literacy ability in three-dimensional topic learning design using Augmented Reality - Erviani, Erviani; Putri, Agustiany Dumeva; Agustiani, Riza; Zahra, Atika; Faisal, Muhammad (Jurnal Pendidikan Matematika RAFA, 2024)
This research aims to produce a learning trajectory on the topic of three dimensions of projection material and describe the numeracy literacy ability of students in class X MAN, using the classroom context through augmented reality technology. The research method used is design research (DR) of the validation studies type. This study is divided into three stages, namely preparing for the experiment, design experiment and the retrospective analysis. The data collection techniques used are observation, interviews, tests, and documentation. The data analysis techniques used were reduction, display, and conclusion drawn. The learning design can attract students' interest and provide new experiences in carrying out mathematics learning. After the learning design went through a series of research stages to produce HLT, which was then implemented and analyzed so that it was suitable for LIT and the results of the analysis also obtained students' numeracy literacy skills as seen from 3 indicators, still experiencing difficulties in indicator 1, namely using various kinds of numbers and symbols related to basic mathematics to solve practical problems in various life contexts everyday.